Wizerunki kobiet w Polskiej Kronice Filmowej w latach 1949–1953 (zarys problemu) - Jędrzejski, Łukasz (Polityka i Społeczeństwo, 2021)
The purpose of the article is presentation Images of Women's in Polish Film Chronicle in the 1949–1953 years. This article is intended to present the following issues: 1) What role in the editorial team of Polish Film Chronicle was played by women? 2) How was the image of women shaped and evaluated in 1949–1953 in PFC? 3) What specific rituals were observed during the celebration of International Women’s Day between 1949–1953?